An Integrated Model of Executive Functioning is Helpful for Understanding ADHD and Associated Disorders. (June 2015) - Crippa, Alessandro; Marzocchi, Gian Marco; Piroddi, Chiara; Besana, Dante; Giribone, Simona; Vio, Claudio; Maschietto, Dino; Fornaro, Emiddio; Repossi, Silvana; Sora, Maria Laura
Objective: The aim of this study is to test the discriminative capacity of executive function (EF) tasks to better define the cognitive functioning of children with ADHD and comorbidities.Method: One hundred four children were presented with a battery of new EF tasks and a rating scale filled out by parents.Results: Preliminary analysis of the neuropsychological tasks revealed the presence of five factors: Speed of Processing, Inhibition, Planning, Execution, and Retrospective Memory. All children with ADHD were impaired in Execution (a measure describing the capacity to achieve a goal). ADHD-only children were specifically impaired in Planning, while ADHD + reading disorder (RD) children were impaired in Speed of Processing and Retrospective Memory. Children with ADHD + oppositional defiant disorder (ODD) did not show impairment in any other EF domains. The five EF processes correlated with the EF Questionnaire.Conclusion: The present study describes different cognitive profiles in children with ADHD with or without comorbid disorders using neuropsychological EF measures.